Should Indonesia Accede to The 1951 Refugee Convention and Its 1967 Protocol? - Liliansa, Dita; Jayadi, Anbar (Indonesia Law Review, 2015)
Being a non-party to the 1951 Convention relating to the Status of Refugees (“1951 Refugee Convention”) and 1967 Protocol relating to the Status of Refugees (“1967 Protocol”), Indonesia does not have legal obligations to provide permanent resettlement for asylum seeker and/or refugee. However, as a transit country for those seeking shelter in Australia, Indonesia undergoes a myriad of issues resulting from illegal entrance by asylum seeker and/or refugee. Besides having neither legal framework nor domestic mechanism to handle asylum seekers and/or refugee, Indonesia’s immigration law identifies every foreigner including asylum seeker and refugee who unlawfully enter Indonesia’s territory into the same box as illegal migrant. It then leads to the arrest of asylum seeker and/or refugee to be put in an over-capacity detention center or other places. This paper will analyze various issues related to asylum seeker and refugee in Indonesia and to weigh whether it is indispensable for Indonesia to accede to the 1951 Refugee Convention and its 1967 Protocol.